The LYRA photometric system and the catalog of photometric reference standard stars. Issue 8 (1st October 2013) - Zakharov, A.I.; Mironov, A.V.; Nikolaev, F.N.; Prokhorov, M.E.; Tuchin, M.S.; Malkov, Oleg Yu.; Rastorguev, Alexey S.
Abstract The 10‐color photometric system for the Russian space photometric experiment LYRA is described. It is shown that the system is effective for the determination of interstellar extinction, separation of supergiants, and evaluation of metallicity. The creation of a large grid of high‐precision photometric standards is one of the most important tasks of the LYRA experiment. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)